Time course and dimensions of postural control changes following neuromuscular training in youth field hockey athletes - Zech, Astrid; Klahn, Philipp; Hoeft, Jon; zu Eulenburg, Christine; Steib, Simon (European journal of applied physiology, 2014)
Injury prevention effects of neuromuscular training have been partly attributed to postural control adaptations. Uncertainty exists regarding the magnitude of these adaptations and on how they can be adequately monitored. The objective was to determine the time course of neuromuscular training effects on functional, dynamic and static balance measures.
Published 10 December 2013
Gesehen am 13.07.2022